T Cell immunity to enterovirus 71 infection in humans and implications for vaccine development - Yee, Isabel Pin Tsin *; Poh, Chit Laa * (Ivy Spring International Publisher, 2018)
Enterovirus 71 (EV-A71) is one of the major pathogens causing hand, foot and mouth disease (HFMD). Some strains can lead to neurological disease and fatality in children. Up to date, there is no FDA-approved vaccine to prevent severe HFMD and mortality. Although the inactivated vaccine has advanced to production in China, lack of long-term protection and the requirement of multiple boosters have necessitated the development of other types of vaccines. Recent studies indicate that cellular and not humoral immunity determines the clinical outcome of EV-A71 infections. High levels of cytokines such as IL-1β, IL-6, IL-10 and IFN-γ tend to correlate with clinical severity in patients with pulmonary edema and encephalitis. The live attenuated vaccine may serve as the preferred choice as it can induce excellent humoral and cellular immunity as well as live-long immunity. Expression of certain HLA alleles such as TNF-α promoter type II (-308 allele), HLA-A33 and HLA-DR17 responses have been linked to severe HFMD. However, the high variability of MHC genes could restrict T cell recognition and be a major obstacle in the design of peptide vaccines. Hence, the development of a T cell universal vaccine (incorporating both CD4+ and CD8+ T cell epitopes) that induces broad, multifunctional and cross-reactive CD8+ T cell responses maybe desirable.